Analysis of Purse Seine Vessel Operations Based at PPI Dufa-Dufa - Kharie, M. Farid; Tangke, Umar; Laisouw, Ruslan; Darmawaty, Darmawaty; Masiyah, Siti (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
Fisheries activities in Ternate City are developing well, this is supported by the operation of the Fish Landing Base (PPI) and the Ternate Nusantara Fishing Port. Information on effective fishing units and operations that have high productivity is important in the development of capture fisheries in PPI Dufa-Dufa, so that purse seine fisheries in PPI Dufa-Dufa is expected to be profitable and sustainable, therefore research on purse seine vessel operations needs to be done by considering all related aspects. The research took place from June to August 2014 at PPI Dufa-Dufa Ternate City by using descriptive analysis and effectiveness and efficiency analysis using scoring method to determine the level of effectiveness and efficiency analysis of purse seine vessel operational activities. The results of the study found that larger vessels (GT more than 20) have higher effectiveness and efficiency values than small vessels (GT less than 20). Purse seine operations at PPI Dufa-Dufa still allow for the development of operational activities, namely the development of new areas for fishing, improving fishing technology and increasing the quality value of catches in the form of training in handling catches